Implementasi Kurikulum Merdeka Dalam Pendidikan Agama Islam - Mutmainnah, Mutmainnah; Rofiq, Ainur (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Education is a process of training and teaching, especially for children and youth, both at school and on campus. With the aim of providing knowledge and developing skills possessed by students. In the Big Indonesian Dictionary education is defined as the process of changing attitudes and behavior of a person or group, in maturing humans through teaching and training. The aim of the study was to analyze the implementation of the independent curriculum at MA Amanatul Ummah and to analyze the implementation of the independent curriculum in motivating students to study Islamic religious education at MA Amanatul Ummah. Qualitative methods will be used in this study. The type of research used is descriptive qualitative, which aims to describe and analyze events, activities and events both individually and in groups. The research results of the Superior MA Amanatul Ummah 03 have succeeded in implementing an independent curriculum with 4 aspects, namely competence, innovation, creativity and work ethic even though in its implementation there are total obstacles such as the lack of using technology learning media such as cellphones and laptops because the Superior MA Amanatul Ummah is a pesantren-based school.